POWER OF LANGUAGE IN EDUCATION - Meisa Fitri Nasution (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2018)
When we speak or write, we â€œtailorâ€ what we say to fit the particular situation in which we are communicating and, at the same time, how we speak or write creates that very situation. We fit our language to a situation or context that ourlanguage, in turn, helped to create in the first placeâ€™ (Gee, 1999: 11). Furthermore, it seems that we always build and rebuild reality not just by dint of the language we employ but through language as discourse, i.e., language used in tandem with non-linguistic cues and symbol systems, tools, actions, interactions, technologies, and particular ways of thinking, feeling, or believing (ibid.). In looking at how power is exercised through language, the capability to refer to real examples that is found, and explained texts. But have a theoretical approach that will enable to interpret language data is presented with in an exam. Among other things, one should look at pragmatics and speech act theory, lexis and semantics (forms and meanings), forms that include or exclude (insiders or outsiders), structures (at phrase, clause and discourse level), forms of address, phatic tokens, as well as structural features of speech, which may be used to exercise or establish power. And in some contexts, one will need to be able to show how rhetorical devices are used to influence an audience